As percepções de educadores sobre a utilização do espaço maker na Educação Básica - Menezes, Maria Eduarda de Lima (2020)
The study developed within the Ph.D. Program in Education: Curriculum by the Pontifical Catholic University of São Paulo aims at comprehending educators’ (teachers and educational technology coordinators) perceptions about using the makerspace in K-12. Maker is a movement that has gained space in the school environment as an extension of the Do it Yourself Culture (DIY). In order to expand on the topic, we developed a Systematic Literature Review (SLR) using four national and international databases as well as PUC’s New Technology on Education data base. This is qualitative research. It was developed in a private and in a public school in the city of São Paulo. We used different research techniques, which included: semi-structured interviews, participant observation in class without interventions and online questionnaires through social media platforms targeted at teachers and technology coordinators throughout the country. In order to organize, treat and analyze the SLR content as well as the empirical data collected, we used the NVivo 12 Pro software, as in addition to the creation of six categories: curriculum, project, maker, teacher, students and challenges. The results show that there is a maker educational proposal in the two schools we analyzed. They are both going through an integration process, once makerspace enables teacher and students to learn and it potentializes the development of socioemotional competences and abilities, such as: autonomy, collaboration, criticism, sharing and creativity. Maker education promotes daily challenges and a continuous resignification of concepts, time, learning and teaching style within this new culture